CONCEPT AND QUALITATIVE PHENOMENOLOGY RESEARCH IN THE FIELD OF ISLAMIC EDUCATION - Lismawati Sihombing; M. Syukri Azwar Lubis (Prodi PAI Sekolah Tinggi Agama Islam Serdang Lubuk Pakam, 2026)
Research is essentially a scientific activity aimed at obtaining accurate knowledge about a particular issue. This study aims to explore qualitative research methods using a phenomenological approach to address problems arising from difficulties that disrupt human life or simply from the innate human curiosity. To address the issues in this study, the researcher employed library research as the primary method. Literature sources serve as the main data source in this study. In the context of this research, phenomenology represents a form of research that stands on its own, where a phenomenon becomes an experience that is revealed. Phenomenological research provides answers to ontological questions, involving specific steps such as determining the location and sources of informants, the approach process, efforts to identify informants, data collection techniques, data analysis steps, and the presentation of research findings.